Gallery of malignancies images as didactic tool in oncology - Ileana Guerra Macías; Rafael Neyra Barros; Aurora López García; Ahmed Adiz Mariño; Argenis Rodríguez Casacaret (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: Malignancies are prevalent affections that demand an early diagnosis for an opportune treatment. The making of an images gallery as teaching means with digital technology constitutes a learning tool of unquestionable value in the oncology specialty. Objective: To make a gallery of malignancies digital images as alternative teaching means for the residents and nursing professionals. Methods: A technological innovation was carried out in Conrado Benítez García Provincial Teaching Oncological Hospital in Santiago de Cuba, during the January-February two-month period, 2023. The study object and action field were the learning resources and the digital images on malignancies, respectively. The theoretical investigation methods (systematizing, experiential and analytic synthetic) and empiric (documental analysis and interviews in questionnaire form to key informants) were combined. Results: As alternative teaching means for medical and nursing teaching, a digital gallery was manually made with 164 malignancies images that included almost all the localizations. Computer science experts, specialists, residents and nurses valued as very appropriate the computer product, based on the scientificity and the technological didactics for the integral academic training. Conclusions: The gallery of digital images constitutes a didactic, motivational, attractive and interesting tool for learning of malignancies; it is an illustrative and utilitarian resource for medical and nursing professional teaching.